ON THE POSSIBILITY OF DEMOCRACY:AN INTERACTION BETWEEN THE WORKS OF JACQUES RANCIÈRE AND MARTIN HEIDEGGER - Monin (University of Toledo), Nick (Intuitio, 2008)
ABSTRACT: In the most general sense, this essay explores a strategy for understanding how modern democracies could become more “democratic.” What is essentially at stake here is a rethinking of the demos, along with its relationship to a polis. In order to do this, I make use of Jacques Rancière’s Disagreement along with Martin Heidegger’s lectures on Höderlin’s hymn Der Ister. I argue that the interactions between these two texts provide rich soil for a radical interpretation of the meaning of “democracy.”KEY WORDS: Democracy. Demos. Disagreement. Polis.